The same and not the same: molecular perovskites and their solid-state analogues. Issue 3 (6th April 2017) - Kieslich, Gregor; Goodwin, Andrew L.
Abstract : We review the crystal chemistry and physics of molecular perovskites, drawing on topical examples of the recent literature. Abstract : There has been enormous interest in ABX3 perovskite-type materials where at least one ion, usually A or X, is replaced with a molecular building unit. In this Minireview we highlight the unique properties that arise as a result of these molecular building units, drawing on topical examples of the recent literature. We focus in particular on phenomena related to low energy lattice modes that tie the molecular building-units to the fascinating properties observed in molecular perovskites.